Risk factors of childhood leukemia - Paulina K. Bangun; Bidasari Lubis; Sri Sofyani; Nelly Rosdiana; Olga R. Siregar (Indonesian Pediatric Society, 2014)
Background The incidence of childhood leukemia has increasedannually. Recent studies have shown that childhood leukemia isinitiated in utero, and have focused on prenatal risk factors suchas birth weight and parental age. Exposure to pesticides andradiation, as well as parental smoking, breastfeeding, and thenumber of older siblings have also been sugges ted as risk factorsfor childhood leukemia.Objective To evaluate possible risk factors for childhood leukemia,including birth weight, parental age, and other risk factors.Methods This case-con trol study was conducted from October2011 to February 2012 in Haji Adam Malik Hospital, Medan .Case subjects were children aged below 18 years and diagnosedwith leukemia. Control subjects were children aged below 18years who were diagnosed with any non-cancerous acute illnessesin this hospital, and individually matched for age and gen der tothe case subject group. Patients and parents were asked to fill astructured questionnaire. Data was analyzed using conditionallogistic regression .Results A total of 140 subjects were eligible, with 70 subjects ineach group. Birth weight 2: 4000 g and maternal age 2:35 yearswere significant risk factors with OR 10.13 (95%CI 1.124 to 91.2 7)and OR 4.98 (95%CI 1.276 to 19.445), respectively. Paternal ageof 2:35 years was not a significant risk factor. Exposure to pesticideswas also noted as another significant risk factor (OR= 6.66; 95%CI2.021 to 21.966) .Conclusion High birth weight, advan ced maternal age, andexposure to pesticides are risk factors of childhood leukemia.